Lexical-semantic field of construction terminology in English language - Nigmatova Farida; Mamatova Feruza (Genius Journals, 2023)
This article focuses on the ways of making architectural and construction terminology and words, their lexical and semantic meaning. nowadays like other spheres, architecture is also developing day by day and of course, as a result of this development, both the number of phrases in this field and also the interest in learning these words has risen. even though the lexemes which are used in architecture are alike in many languages, there some distinctive features in their lexical meaning and word formation. In the following article there are given some opinions about word-forming suffixes and their usage in different parts of speech
Keywords: lexical-semantic features; terminology; architectural terminology; architectural discourse